(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The aggravation of the socio-political situation in the world, the geopolitical struggle between some forces, in order to ensure gross security, requires the training of skilled servicemen who can use modern military technologies. Therefore, in addition to increasing combat readiness, professional and social responsibility of servicemen, special attention is paid to the formation in them of a sense of self-consciousness and patriotism. The formation of new ways of raising the national spirit of servicemen, the development of new methodological approaches to the integration of the essence of the national ideology into the consciousness of them is of paramount importance in the current period, when threats against national spirituality in the information space are on the rise. The article considers the fact that national self-awareness is an important factor in the formation and promotion of the national spirit in servicemen, the peculiarities of national self-awareness, historical self-awareness and its importance in the development of mankind.